Reef Beat education series: river to reef - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2005)
The 2005 Reef Beat education series — river to reef, provides students and teachers with information about the connectivity between rivers and the Great Barrier Reef. Activities and posters included in this resource enable students and teachers to learn more about their local waterways and the Great Barrier Reef, while also helping them to become involved in the recovery of our precious land and reef communities by assisting to improve the quality of water entering the Reef. The 2005 Reef Beat education series also featured in the NIE section of the Cairns Post.
Keywords: People and the Reef; Ecosystems; Water quality; Schools; Reef-wide